Medium- and low-voltage planning of radial electric power distribution systems considering reliability - Rupolo, Diogo [UNESP]; Pereira, Benvindo Rodrigues; Contreras, Javier; Mantovani, José Roberto Sanches [UNESP] (Institution of Engineering and Technology (IET), 2017)
This study proposes a new methodology to carry out distribution network planning considering medium-voltage (MV) and low-voltage (LV) systems. The integrated planning problem of a MV/LV distribution system is formulated as a mixed-integer non-linear program and aims at minimising investment (substations, transformers, conductors, poles, and structures), operating, and reliability costs. The coupling constraints between MV/LV networks are represented by MV/LV modelling transformers through the power flow equations. The mathematical model is solved by the general variable neighborhood search metaheuristic method, which allows us to explore the search space through intensification and diversification criteria. The proposed methodology is applied in a system with 50 buses at the MV level and 410 buses at the LV level.